2018
DOI: 10.1097/pcc.0000000000001506
|View full text |Cite
|
Sign up to set email alerts
|

Interhospital Transport of Critically Ill Children to PICUs in the United Kingdom and Republic of Ireland: Analysis of an International Dataset*

Abstract: Variations exist in United Kingdom and Ireland services for critically ill children needing interhospital transport. Future studies should assess the impact of these variations on long-term patient outcomes taking into account treatment provided prior to transport.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 18 publications
1
39
0
Order By: Relevance
“…24 Emergency and unplanned admissions to paediatric ICUs equal approximately 12,000 per year of which approximately 6000 are carried out by specialist transport teams. 25 Fifty six per cent (25/45) of the infants in this study had an antenatal diagnosis of which 92% (23/25) were born at the tertiary maternity unit. This is consistent with findings of previous studies that showed that the detection rate for infants with transposition of the great arteries is between 41 and 84%.…”
Section: Discussionmentioning
confidence: 78%
“…24 Emergency and unplanned admissions to paediatric ICUs equal approximately 12,000 per year of which approximately 6000 are carried out by specialist transport teams. 25 Fifty six per cent (25/45) of the infants in this study had an antenatal diagnosis of which 92% (23/25) were born at the tertiary maternity unit. This is consistent with findings of previous studies that showed that the detection rate for infants with transposition of the great arteries is between 41 and 84%.…”
Section: Discussionmentioning
confidence: 78%
“…Multiple attempts at endotracheal intubation are associated with an increased complication rate . A team of skilled and experienced clinicians can safely undertake endotracheal intubation in the retrieval environment with a high first attempt success rate …”
Section: Discussionmentioning
confidence: 99%
“…This has been demonstrated in both pediatric and studies in adult patients. [21415161718] The additional crude mortality rates in critically ill children because of interfacility transport in developed countries are reported to be in the range of 4%–10%. [192021] We also found increased mortality and worsened SI as well as high serum lactate at admission in this group of children.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, most referrals do not take into account – weather conditions, time to transport, or availability of specialized equipment or personnel trained in pediatric transport. [2] Many countries including India have national ambulance service or emergency response system that are equipped with lifesaving equipments and can provide basic treatment to a patient before arrival in the hospital. [3] However, few patients/facilities are reported to use these services for various reasons.…”
Section: Introductionmentioning
confidence: 99%